2021
DOI: 10.3390/ijerph18083866
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Body Image, Insight, and Mental Health Confidence on Medication Adherence in Young Adult Women with Mental Disorders

Abstract: The aim of this descriptive study was to investigate the impact of body image, insight, and mental health confidence on medication adherence among young adult women with mental disorders. Data collection occurred from August to September 2018. The study participants were 147 young adult women aged 19 to 45 with mental disorders who were psychiatry outpatients either getting treatment in general hospitals located in Seoul and Gyeonggi Province or receiving rehabilitation therapy through local mental health welf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Despite overweight and obesity having metabolic effects, as well as causing changes in the pharmacodynamics of medications, our results also suggest they are associated with low-moderate adherence only in women. We might explain this gender-differential finding as a consequence of women having a poor body self-perception as BMI increases [ 38 ], and in turn, such self-perception might be associated with poor medication adherence [ 39 ]. BMI extracted from physical examination in women seems to be valuable predictor regarding medication use.…”
Section: Discussionmentioning
confidence: 99%
“…Despite overweight and obesity having metabolic effects, as well as causing changes in the pharmacodynamics of medications, our results also suggest they are associated with low-moderate adherence only in women. We might explain this gender-differential finding as a consequence of women having a poor body self-perception as BMI increases [ 38 ], and in turn, such self-perception might be associated with poor medication adherence [ 39 ]. BMI extracted from physical examination in women seems to be valuable predictor regarding medication use.…”
Section: Discussionmentioning
confidence: 99%
“…The present study found a relationship between medication adherence and psychosocial adjustment to body weight, image, and self‐esteem. 27.7% of patients with schizophrenia in Korea were nonadherence to medication regimens due to weight gain (Lee & Jang, 2021). Verdoux et al (2021) found that patients with psychosis who had low adherence to treatment were more likely to present with poor self‐esteem.…”
Section: Discussionmentioning
confidence: 99%
“…One study explored antipsychotic medication adherence in people diagnosed with schizophrenia and reported a significant positive relationship between self-reported medication adherence and body image (r = 0.31, p < 0.05) 41 . A further study in women living with psychotic conditions including schizophrenia and bipolar showed a negative correlation between body image and medication adherence (r = −0.616, p < 0.001) using a scale where higher scores indicated poorer body image 42 .…”
Section: Medication Adherencementioning
confidence: 91%